2015
DOI: 10.1093/rheumatology/kev128
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided synovial biopsy: a systematic review according to the OMERACT filter and recommendations for minimal reporting standards in clinical studies

Abstract: USG-SB can be regarded as a valuable tool for large-scale synovial tissue sampling. Standardization of the techniques of USG-SB and tissue processing is needed. Future research should focus on the reliability, responsiveness and feasibility of this procedure in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 31 publications
2
33
0
1
Order By: Relevance
“…Importantly, the morbidity associated with the biopsy procedure was quite low, with only a single hemarthrosis, and no other complications reported during a mean followup of nearly 3 years. This study not only confirms the previous works that have used US-guided synovial biopsies, but extends their findings and provides support for general use in the clinic 8,12,13,14,15 .…”
supporting
confidence: 89%
“…Importantly, the morbidity associated with the biopsy procedure was quite low, with only a single hemarthrosis, and no other complications reported during a mean followup of nearly 3 years. This study not only confirms the previous works that have used US-guided synovial biopsies, but extends their findings and provides support for general use in the clinic 8,12,13,14,15 .…”
supporting
confidence: 89%
“…60 This incidence is reproducible at other centres where the overall complication rate was shown to be less than 0.3%.Similarly, an overall major complication rate is reported as 0.4% for ultrasound guided biopsy procedures. 61 One study of biopsies in RA patients taken from both an inflamed knee joint and a small joint, showed similar mean cell numbers for all markers investigated in the synovial sublining in both sample sources. 62 Of further note, patients with clinically evident disease manifest at small joints have been shown to have similar abnormalities in clinically uninvolved knee joints, albeit at lower expression levels.…”
Section: Retrieving Synovial Tissue Samplesmentioning
confidence: 97%
“…Both have been shown to be safe, and well tolerated by the patients (22). The first method requires a single portal with a flexible or rigid biopsy forceps.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that microscopic measurements of synovial inflammation does not differ between biopsies taken blindly or under guided vision (19 (20,21). This technique has the benefit of being low cost, rapidly and easily performed without the need for exposing the patient to ionising radiation, and is widely available (22). It is more practical than arthroscopy for biopsying small joints and allows guidance to the thickest synovial zones.…”
Section: Introductionmentioning
confidence: 99%